2002
DOI: 10.1089/089277902760367421
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Percutaneous Access to the Kidney: Comparison with Standard Manual Access

Abstract: Purpose: To evaluate the efficiency, accuracy, and safety of robotic percutaneous access to the kidney (PAKY) for percutaneous nephrolithotomy in comparison with conventional manual techniques. Materials and Methods:We compared the intraoperative access variables (number of access attempts, time to successful access, estimated blood loss, complications) of 23 patients who underwent robotic PAKY with the remote center of motion device (PAKY-RCM) with the same data from a contemporaneous series of 23 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 6 publications
0
45
0
3
Order By: Relevance
“…A general review of robotic systems for image-guided interventions can be found in. 23,24 The systems presented for minimally-invasive needle insertion into abdominal organs include those introduced by Su et al, 25 Kim et al, 26 Kettenbach et al 27 and Maurin et al 28 Several papers have been published on the accuracy of medical robots 27-29 as well as on the comparison between conventional and robotic-assisted medical interventions, 25, 30 yet, integration of a medical robot with an existing soft tissue navigation system to reduce the operator error has -to our knowledge -not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A general review of robotic systems for image-guided interventions can be found in. 23,24 The systems presented for minimally-invasive needle insertion into abdominal organs include those introduced by Su et al, 25 Kim et al, 26 Kettenbach et al 27 and Maurin et al 28 Several papers have been published on the accuracy of medical robots 27-29 as well as on the comparison between conventional and robotic-assisted medical interventions, 25, 30 yet, integration of a medical robot with an existing soft tissue navigation system to reduce the operator error has -to our knowledge -not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, they have been applied to real-time, percutaneous, image-guided interventions such as fluoroscopically guided nephrostomy tube placement and computed tomography (CT)-guided biopsy and thermal ablation (6,7).…”
mentioning
confidence: 99%
“…It was attached to the side rail of the operating table, and incorporated a radiolucent needle grasping disc at the distal end of the arm (8). The PAKY (percutaneous access to the kidney) system and later PAKY-RCM (remote center of motion) system were improvements on the original design: the passive robotic arm was improved by adding an electronic needle insertion device and the ability to position the needle by remote control (9,10).…”
Section: Basic and Translational Urology Doi: 101590/s1677-553820100mentioning
confidence: 99%